A Detail Story About Phytoconstituents and Clincial Uses of Narikela (Coconut, Cocos Nucifera): Drug Review - Mishra Akanksha; Agrawal Neeraj; Chandravanshi Lowkesh; Rathia Satyawati; Dushyant; Bhatt Lalit Mohan (AYUSHDHARA, 2023)
The Arecaceae plant species Cocos nucifera (L.), known as the "coconut tree," is the most widely distributed fruit tree in nature. Minerals, plants, and animals have traditionally been the primary suppliers of medications, and people have employed medicinal plants therapeutically throughout history. In ancient writings, Ayurveda describes the usage of Narikela (Cocos nucifera Linn., Arecaceae) for the treatment of several diseases. Lauric acid, capric acid and caprylic acid are some of the most important fatty acids found in coconut. There are only two main sources of lauric acid in the human diet: coconut and human breast milk. In addition to having antibacterial and antiprotozoal properties, lauric acid also strengthens the immune system and has an anti-inflammatory effect. This article covers the broad aspect of properties and therapeutic actions of different useful parts of coconut tree.